Brachypodium distachyon exhibits compatible interactions with Oculimacula spp. and Ramularia collo‐cygni, providing the first pathosystem model to study eyespot and ramularia leaf spot diseases. (6th August 2013) - Peraldi, A.; Griffe, L. L.; Burt, C.; McGrann, G. R. D.; Nicholson, P.
<x xml:space="preserve">Abstract</x> Brachypodium distachyon (Bd) has established itself as an essential tool for comparative genomic studies in cereals and increasing attention is being paid to its potential as a model pathosystem. Eyespot and ramularia leaf spot (RLS) are important diseases of wheat, barley and other small‐grain cereals for which very little is known about the mechanisms of host resistance despite urgent requirements for plant breeders to develop resistant varieties. This work aimed to test the compatibility of interaction of two Bd accessions with the cereal pathogens Oculimacula spp. and Ramularia collo‐cygni, the causal agents of eyespot and RLS diseases, respectively. Results showed that both Bd accessions developed symptoms similar to those on the natural host for all pathogen species tested. Microscopy images demonstrated that R. collo‐cygni produced secondary conidia and both Oculimacula spp. formed characteristic infection structures on successive tissue layers. Visual disease assessment revealed that quantitative differences in disease severity exist between the two Bd accessions. The results presented here provide the first evidence that Bd is compatible with the main causal agents of eyespot and RLS diseases, and suggest that future functional genetic studies can be undertaken to investigate the mechanisms of eyespot and RLS disease resistance using Bd.